2012
DOI: 10.1097/scs.0b013e31825d05bb
|View full text |Cite
|
Sign up to set email alerts
|

Orthognathic Surgery for Obstructive Sleep Apnea

Abstract: This article is dedicated to the senior author Dr. Henry K. Kawamoto, Jr, who pioneered the use of orthognathic surgery to treat severe obstructive sleep apnea in 1981. Since that time, his techniques for maxillomandibular advancement have been revised and expanded for improved surgical success. Obstructive sleep apnea is a growing public health concern because it can cause hypertension, cardiac arrhythmias, heart attack, stroke, and, in rare circumstances, sudden death if untreated. When less invasive options… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Initial investigations on airway patency, function and disorders utilizing CBCT have provided preliminary answers, including dimensions of normal airway anatomy in adults, 122,126 relationship Dentomaxillofac Radiol, 44,20140282 birpublications.org/dmfr of 2D to 3D measurements, 127 differences in airway morphology in subjects with OSA and non-OSA, [128][129][130] the effects of extractions on 3D pharyngeal volume and structure, 131 and the consequences of RME [132][133][134][135] and orthognathic surgery on airway dimensions. 136,137 Several of these studies show no relationships between 2D linear dimensions and 3D cross-sectional areas of the airway, which suggests that the use of 2D data may not be valid for assessing airway patency. Early thinking in orthodontics suggested that a constricted pharyngeal airway may contribute to mouth breathing in children, which then would lead to a steep mandibular plane angle and an anterior open bite tendency.…”
Section: Utilization Of Cbct For Orthodontic Treatment Outcomes Diagmentioning
confidence: 99%
“…Initial investigations on airway patency, function and disorders utilizing CBCT have provided preliminary answers, including dimensions of normal airway anatomy in adults, 122,126 relationship Dentomaxillofac Radiol, 44,20140282 birpublications.org/dmfr of 2D to 3D measurements, 127 differences in airway morphology in subjects with OSA and non-OSA, [128][129][130] the effects of extractions on 3D pharyngeal volume and structure, 131 and the consequences of RME [132][133][134][135] and orthognathic surgery on airway dimensions. 136,137 Several of these studies show no relationships between 2D linear dimensions and 3D cross-sectional areas of the airway, which suggests that the use of 2D data may not be valid for assessing airway patency. Early thinking in orthodontics suggested that a constricted pharyngeal airway may contribute to mouth breathing in children, which then would lead to a steep mandibular plane angle and an anterior open bite tendency.…”
Section: Utilization Of Cbct For Orthodontic Treatment Outcomes Diagmentioning
confidence: 99%
“…[ 11 ] Kawamato seems to have pioneered the maxillomandibular advancement technique for treating OSAS. [ 12 ] Maxillomandibular advancement decreases the collapsibility of the velopharyngeal and suprahyoid musculature and improves lateral pharyngeal wall collapse, all of which have been shown to be significant components contributing to the upper airway obstruction in OSA. [ 13 ] The outcome of maxillomandibular advancement has been extensively reported, with success rates of 57% to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual and controlled elongation during distraction osteogenesis allows for tissue regeneration and repair to occur within the skeleton and the soft tissue associated with it, including the muscles, subcutaneous tissue, and skin. 41 Especially in the case of severe midface hypoplasia and/or upper airway obstruction 42 often seen in cleft patients, orthognathic surgery may be planned with the use of internal or external distractors. The reasons for the use of distraction within orthognathic surgery are manifold but may include concern for the increased risk of bony relapse with anticipated large maxillary or mandibular advancements, a deficient or nonpliable soft tissue envelope, or the need to provide additional functional or aesthetic benefit beyond the maxillary-mandibular relationship (e.g., exophthalmos due to shallow orbits, central midface deficiency with shortened nasal bones, etc.).…”
Section: Anatomic and Technical Considerationsmentioning
confidence: 99%